Enhancing disaster prevention learning through human-centered design: Students’ learning cognition and enjoyment in informal educational settings - Lin, Li-Chun; Chang, Mei-Chen; Yang, Han-Chung; Wei, Meng-Chun (International journal of disaster risk reduction, 2024)
This study employs the human-centered design strategy to design disaster prevention education activities, aiming to explore the changes in students' learning cognition and enjoyment before and after participating in these activities. The National Science and Technology Museum, located in southern Taiwan. Its primary objectives encompass the collection of scientific and technological artifacts, the presentation of scientific and technological themes, the advancement of scientific and technological education, and the provision of opportunities for public leisure and lifelong learning. The research focused on 170 elementary school students from grades G3 to G6 who participated in the disaster prevention education of soil and water conservation activity at the National Science and Technology Museum. Pre- and post-tests were conducted to assess disaster prevention learning cognition, and surveys and interviews were used to gauge the joy experienced during disaster prevention learning. The research findings indicate that after participating in disaster prevention education activities, students showed significant improvement in disaster prevention learning cognition. The primary sources of learning enjoyment were closely observing cultural relics and actively engaging with teaching aids. The human-centered design plan can complement the school's disaster prevention education curriculum and address issues such as low student interest, a sense of distance, and a lack of deep impression regarding disaster prevention.